PENGARUH KOMPETENSI PEDAGOGIK GURU, SUPERVISI AKADEMIK KEPALA SEKOLAH, DAN DISIPLIN KERJA TERHADAP KINERJA GURU - Sukamsinah; Supriyoko; Rejokirono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to identify and analyze the effect of teacher pedagogical competence, school principal's academic supervision, joint work discipline on the performance of elementary school teachers in Cluster 1 Kapanewon Wates, Kulon Progo Regency in 2022/2023, Knowing and analyzing the influence of teacher pedagogical competence on teacher performance, knowing and analyzing the influence of the principal's academic supervision on teacher performance, and knowing and analyzing the influence of work discipline on teacher performance. This study uses a quantitative approach. The population of this study was all Cluster 1 Kapanewon Wates teachers, Kulon Progo Regency, totaling 72 people. Data collection using a questionnaire. Data analysis used multiple linear regression analysis techniques. The results of the study show that there is a positive and significant influence between teacher pedagogic competence, academic supervision, work discipline jointly on teacher performance, there is a positive and significant influence between teacher pedagogic competence on teacher performance, there is a positive and significant effect between school principal academic supervision on teacher performance, there is a positive and significant influence between work discipline on teacher performance